A new species and a record of Bdellidae (Acari: Trombidiformes: Bdelloidea) from Iran - Paktinat-Saeij, Saeid; Bagheri, Mohammad; Hernandes, Fabio Akashi [UNESP] (Systematic and Applied Acarology Society, 2016)
Odontoscirus mazandaranensis sp. nov. is described and illustrated based on female, male and tritonymph from Mazandaran province, Iran. Also, Trachymolgus purpureus Fisher & Dowling, 2011 is reported for the first time from Iran.
Keywords: Mazandaran Province; Odontoscirinae; predatory mites; Prostigmata; systematic